2021
DOI: 10.1007/s00068-021-01825-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urinary extravasation after non-operative management of traumatic renal injury: a multi-center retrospective study

Abstract: Purpose Urinary extravasation is one of the major complications after non-operative management of traumatic renal injury and may lead to urinary tract infection and sepsis. The purpose of this study was to evaluate these factors in patients with traumatic renal injury. Methods This was a multi-center, retrospective, observational study performed at three tertiary referral hospitals in Osaka prefecture. We included patients with traumatic renal injury trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The relationship between urinary tract tissues regarding internal pressure can explain the pathophysiology of urinary extravasation. In our case, when renal pelvic pressure rises due to stone impaction, it causes microscopic fissures in the anatomically weakest part of the renal calyx [8,9]. As a result, urine overflows outside the renal pelvis.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The relationship between urinary tract tissues regarding internal pressure can explain the pathophysiology of urinary extravasation. In our case, when renal pelvic pressure rises due to stone impaction, it causes microscopic fissures in the anatomically weakest part of the renal calyx [8,9]. As a result, urine overflows outside the renal pelvis.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, pressures >30-45 mmHg cause extrarenal overflow [10]. Although extrarenal overflow may occur at 20 mmHg, it may not occur at 100 mmHg [8,9]. This indicates that the speed of increase in renal pelvic pressure is more important than absolute renal pelvic pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complications of this method are those associated with any minimally invasive surgical procedure: vascular injury, damage to nearby organs, and infection [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The Society of Cardiovascular and Interventional Radiology and the American College of Radiology have shown that percutaneous nephrostomy is associated with less than 4% major bleeding or septic shock [ 17 ].…”
Section: Introductionmentioning
confidence: 99%